Visions of electric media : television in the Victorian and machine ages - Roberts, Ivy (2019)
Visions of Electric Media is an historical examination into the early history of television, as it was understood during the Victorian and Machine ages. How did the television that we use today develop into a functional technology? What did Victorians expect it to become? How did the 'vision' of television change once viewers could actually see pictures on a screen? We will journey through the history of 'television': from the first indications of live communications in technology and culture in the late nineteenth century, to the development of electronic televisual systems in the early twentieth century. Along the way, we will investigate the philosophy, folklore, engineering practices, and satires that went into making television a useful medium.